THE CORRELATIONS AMONG READABILITY LEVEL OF TEXTS, READING HABIT, AND READING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF MTS AL-QUR’AN HARSALLAKUM BENGKULU - Husna Husna (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2016)
Abstract: The low reading performance of Indonesian students is caused by some factors, namely, the degree of difficulty of the texts or readability level, reading habit, and reading achievement. This study was conducted using correlational research design to know the correlation among readability level of the texts, reading habit, and reading achievement of the eight grade students of MTs Al-Quran Harsallakum Bengkulu. This study involved the eighth grade students of MTs Al-Quran Harsallakum Bengkulu (112 students) in academic year 2014/2015. The sample of this study was 60 students. Test of readability level of the texts, reading habit questionnaire, and reading achievement test were used in order to collect the data for this study. The findings of this study showed that there was a positive  significant  correlation  (r=0.925)  between  readability  level  of  the  texts  and reading achievement. There was also a positive significant correlation (r=0.890) between reading habit and reading achievement and there was a positive significant correlation (r=0.992) between readability level of the texts and reading habit. This study also showed that readability level of the texts gave the contribution to reading achievement (R-Square=0.855) and reading habit gave the contribution to reading achievement (R-Square=0.792).Keywords: correlations, readability level of the texts, reading habit, reading achievement.